The Possible Consequences of Accession of Kazakhstan to the World Trade Organization - RAKHIMBAYEVA, Assemgul; MADIYAROVA, Diana; BLOKHINA, Tatiana A.; KORABAYEV, Beibit (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
The recent accession of the Republic of Kazakhstan to the World Trade Organization in 2015 became the hot topic of public discussion within the country. Therefore, in recent years the outcome of the negotiation process and conditions of accession to the WTO has attracted significant public and political attention in Kazakhstan. The authors compare Kazakhstan commitments with those of the other countries that have recently acceded to the WTO. The goal of the research is to realize opportunities of the WTO accession to Kazakhstan. The authors outline the problems the Kazakhstani Government should radically solve in order to reduce the amount of state business, including the proportion of products manufactured at the state-owned enterprises, to determine the optimal size of government in order to achieve high rates of economic growth. The future generation of Kazakhstan should not regret about the fact that the government of the 1995-2015 years left a legacy of ‘restricted conditions’ for entering to the ‘club’ 30 most developed in the world.
Keywords: World Trade Organization, WTO, World Bank, UNCTAD, economic policy, international trade, multinational companies, accession, partnership, integration